Preparing the enterprise information environment for the digital economy - I. M. Morozova; S. G. Dembitsky; O. N. Zotikova; V. A. Senkov (Вестник университета)
The article provides a brief overview of statistical materials on surveyed Russian organizations in terms of the use of information and communication technologies. The results of the analysis of their use of information and communication technologies allow us to state that a number of enterprises have basic technical equipment and modern digitalization technologies, the use of which is necessary for fruitful functioning in the information environment, for further digitalization of production, economic, financial, economic and other activities. The development of the digital economy of enterprises is influenced by their financial condition. The presented dynamics of increasing costs for the creation and implementation of information and communication technologies illustrates that enterprises are purposefully preparing the information environment for the application of the achievements of the digital economy. To overcome emerging barriers in the development of the digital economy using information and communication technologies, enterprises need to solve a set of tasks, in particular, due to compliance with the requirements of information and financial and economic security, interconnection and digital combination of software packages when automating activities.